Application of Compound Polymyxin B Ointment in the Treatment of Chronic Refractory Wounds. (September 2022) - Tang, Jiajun; Guan, Haonan; Dong, Wei; Liu, Yingkai; Dong, Jiaoyun; Huang, Lifang; Zhou, Jingqi; Lu, Shuliang
The purpose of this study was to investigate the clinical efficacy of compound polymyxin B ointment for treating chronic refractory wounds. A retrospective analysis was performed on 111 patients who underwent chronic refractory wound treatment. Patients were divided into 2 groups, with 45 patients included in the experimental group (compound polymyxin B group) and 66 patients included in the control group (silver sulfadiazine group). After thorough debridement in both groups, either compound polymyxin B ointment or silver sulfadiazine cream was evenly applied to the patient's wound and covered with sterile gauze. In both groups, dressing changes were dependent on the wound's condition and secretions. Using the Bates-Jensen Wound Assessment Tool (BWAT), patients in both groups were scored, after which wound healing, infection, and healing time were compared. There was no significant difference in BWAT scores between the 2 groups on the 7th or 14th day; however, on the 21st day, the BWAT score in the experimental group was significantly lower than that of the control group. The difference was statistically significant ( P < .05). There was no significant difference in the BWAT-I scores between the 2 groups on the seventh day. The healing time in the experimental group was significantly shorter than that of the control group, and the difference was statistically significant ( P < .05). For the treatment of chronic refractory wounds, thorough debridement followed by compound polymyxin B ointment topical application can reduce and control wound infection effectively and accelerate the process of wound repair.